Severe Hyperthyroidism Complicated by Agranulocytosis Treated with Therapeutic Plasma Exchange: Case Report and Review of the Literature. (10th January 2018) - Garla, Vishnu; Kovvuru, Karthik; Ahuja, Shradha; Palabindala, Venkatataman; Malhotra, Bharat; Abdul Salim, Sohail
Abstract : Aim. To present a case of Graves' disease complicated by methimazole induced agranulocytosis treated with therapeutic plasma exchange (TPE) and review of the literature. Case Presentation . A 21-year-old patient with a history of Graves' disease presented to the endocrine clinic. His history was significant for heat intolerance, weight loss, and tremors. Upon examination he had tachycardia, smooth goiter, thyroid bruit, and hyperactive reflexes. He was started on methimazole and metoprolol and thyroidectomy was to be done once his thyroid function tests normalized. On follow-up, the patient symptoms persisted. Complete blood count done showed a white blood cell count of 2100 (4000–11, 000 cells/cu mm) with a neutrophil count of 400 cells/cu mm, consistent with neutropenia. He was admitted to the hospital and underwent 3 cycles of TPE and was also given filgrastim. He improved clinically and his thyroxine (T4) levels also came down. Thyroidectomy was done. He was discharged on levothyroxine for postsurgical hypothyroidism. Conclusion . Plasmapheresis may be useful in the treatment of hyperthyroidism. It works by removing protein bound hormones and also possibly inflammatory cytokines. Further studies are needed to clarify the role of various modalities of TPE in the treatment of hyperthyroidism.